Usability Evaluation of Virtual Museum Environment: A Case Study in Terengganu State Museum, Malaysia - Normala, Rahim; Norkhairani, Abdul Rawi; Roslinda, Muda; Tengku Siti Meriam, Tengku Wook; Nor Azan, Mat Zin (2016)
This paper conducted the usability evaluation of Virtual Museum Environment (VME) for Terengganu State Museum. The model that has been applied in this research was based on User-Centered Design (UCD) involving many users in every stage. User testing was performed online using questionnaire with a total of 52 respondents. The usability evaluation measured three factors that include navigation, manipulation and system control. Three usability elements tested in this study were: ease of use, efficiency and users’ satisfaction. Overall, the mean score obtained for each element that is over the scale of 4.00 indicates high usability of the VME prototype.